Administration of GnRH at insemination in repeat breeding dairy cows: improved pregnancy rates, hormone secretion, and luteal function - Jeffrey S. Stevenson; M. O. Mee; Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1991)
Administering saline to 14 repeat breeders or 100 Î¼g GnRH to 38 repeat breeders resulted in a greater (P=.07) proportion of pregnancies at 42 to 56 days after third service and fewer (P<.05) lost pregnancies during the 25- to 38-day period of placentation. Concentrations of LH in serum of six repeat breeders previously given 100 Î¼g GnRH 12 hr after detected estrus (day 0) were reduced (P<.05) on days 1, 3, and 8 after estrus compared to those in six cows previously given saline at estrus. Concentrations of FSH were similar among treatment groups on days 1 and 3, but were elevated (P<.05) on day 8 in GnRHtreated cows. Furthermore, all six GnRH-treated cows had detectable FSH pulses on day 8 compared to two of six control cows. Concentrations of progesterone in serum were elevated (P<.05) on days 8 to 10 after estrus in GnRH-treated cows, and their corpora lutea obtained on day 10 after estrus and treatment contained a greater (P<.05) proportion (31 vs. 14%) of large-diameter (21 to 37 Î¼m) luteal cells and a lesser (P<.05) proportion (69 vs. 86%) of small-diameter (10 to 17 Î¼m) luteal cells than corpora lutea from control cows. In vitro production of progesterone in response to LH was reduced (P<.05) in luteal tissue obtained on day 10 after estrus from cows previously treated with GnRH at estrus compared to cows given only saline. It appears that pregnancy rates are improved in repeat breeders given GnRH at the time of insemination as a result of increased secretion of progesterone related to alterations in the morphology and function of the corpus luteum, as well as possible influences of FSH secretion from the pituitary gland.; Dairy Day, 1991, Kansas State University, Manhattan, KS, 1991;
Keywords: Dairy Day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-175-S; Report of progress (Kansas Agricultural Experiment Station); 640; Dairy; Pregnancy rates; Progesterone; LH; FSH; GnRH; Luteal function